KESEJAHTERAAN PSIKOLOGIS REMAJA PANTI ASUHAN SIMO BOYOLALI - Argo Muhammad Saputra; Faqih Purnomosidi; Anniez Rachmawati Musslifah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Psychological well-being is crucial for life. Psychological well-being will be reflected in good adaptation and communication. A factor of psychological well-being is social support. Orphanage children will experience difficulties in establishing relationships with their colleagues and cannot recognize themselves in depth without social support. This study aims to determine the psychological well-being of adolescents at the Simo Boyolali orphanage. The research method used qualitative methods. The results of seven respondents show that the psychological well-being of the adolescents at the Simo Boyolali orphanage is classified as very good. It is proved by observations and interviews from researchers and data analysis shows that the psychological well-being of adolescents at the Simo Boyolali orphanage is fulfilled. Keywords: Social Support, Psychological Well-being, Orphanage Adolescents